UJI AKTIVITAS EKSTRAK METANOL BIJI JUWET (SYZYGIUM CUMINI (L.) SKEELS) SEBAGAI ANTIHIPERURISEMIA PADA MENCIT HIPERURISEMIA - Ulya, Tuhfatul; Masruroh, Ika Nur; Muslichah, Siti; Ningsih, Indah Yulia (Pharmaceutical and Traditional Medicine, 2022)
The purpose of this research was to study the activity of Syzygium cumini seed extract as antihyperuricemics agents on hyperuricemic male Balb-C mice. Twenty four male mice were divided into 6 groups, i.e the first group as a normal control K(N); the second group as a negative control K(-) was treated with CMC Na 1% 0,2 ml/20g/BW orally; the third group as a positive control K(+) was treated with allopurinol 10 mg/kg BW orally; the fourth to sixth groups (P1, P2, and P3) were treated with 200, 400, and 800 mg/kg BW methanol extract of Syzygium cumini seed orally for 8 days. Inducing performed using chicken liver juice 0,2 % b/v for 4 days, melinjo 10 % b/b of standart feed mice for 12 days, and potassium oxonate 250 mg/kg BW i.p was induced in 2 hours before the blood samples collection. The blood samples was taken from vena ophtalmicus. The concentration of uric acid was determined with FS DHBSA. Data was analyzed using One Way Anova dan LSD test. The result showed that activity of methanol extract of Syzygium cumini seed has significant effect (p<0,05) in reducing the concentration of uric acid in mice. The substances estimated has antihyperuricemic activity were flavonoid, alkaloid, terpenoid, saponin, and tanin.